Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1136/rmdopen-2019-000906
|View full text |Cite
|
Sign up to set email alerts
|

Polymyalgia rheumatica-like syndrome from checkpoint inhibitor therapy: case series and systematic review of the literature

Abstract: ObjectiveTo assess whether the polymyalgia rheumatica (PMR)-like syndrome reported as an immune related adverse event (irAE) from checkpoint inhibitor therapy is consistent with the 2012 European League Against Rheumatism (EULAR)/American College of Rheumatology (ACR) provisional criteria for PMR.MethodsThe cases were derived from two sources. Group 1 represents reported cases from three contributing centres. Group 2 was derived from a systematic review of the literature searching for all cases reported as PMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 10 publications
0
51
2
1
Order By: Relevance
“…This percentage was higher (55%) for PsA (6/11), as well as in a recent series of PMR-like syndrome (37/49; 75%). 79 The first observation of recurrent pseudogout flares 7 to 10 days after each nivolumab infusion has been recently reported. 80 Several cases of myositis have been reported, with frequent limb-girdle myalgia and weakness that may mimic a PMR-like condition.…”
Section: Points To Considermentioning
confidence: 99%
“…This percentage was higher (55%) for PsA (6/11), as well as in a recent series of PMR-like syndrome (37/49; 75%). 79 The first observation of recurrent pseudogout flares 7 to 10 days after each nivolumab infusion has been recently reported. 80 Several cases of myositis have been reported, with frequent limb-girdle myalgia and weakness that may mimic a PMR-like condition.…”
Section: Points To Considermentioning
confidence: 99%
“…Arthritis Inflammatory arthritis occurs in approximately 4% of patients treated with ICIs and most commonly presents as a symmetrical polyarthritis resembling rheumatoid arthritis 77. Other presentations include polymyalgia rheumatica and oligoarthritis with or without tenosynovitis 77787980. Rheumatoid factor and anti-citrullinated peptide antibodies occur in a minority of patients 7981.…”
Section: Clinical Presentation Of Checkpoint Inhibitor Associated Autmentioning
confidence: 99%
“…A prospective study of 210 patients [12] and a large retrospective study in Mayo clinic [26] provide data that indicate a somewhat lower prevalence of the syndrome, below 1%. Calabrese et al collected 49 reported cases of PMR-like syndrome in patients on ICI therapy, analyzing data from three major rheumatology centers from USA and Europe along with a systematic review of the literature [32]. It is noteworthy that 25% of the cases did not fulfill the preliminary 2012 European League Against Rheumatism/American College of Rheumatology (EULAR/ACR) criteria for PMR.…”
Section: Polymyalgia Rheumaticamentioning
confidence: 99%